PERENCANAAN EKONOMI PESANTREN BERBASIS KEMANDIRIAN DAN PEMBERDAYAAN: STUDI EMPIRIS DI MAMBAUL KHOIRIYATIL ISLAMIYAH BANGSALSARI-JEMBER - Camelia Camelia; Irmatus Sholihah; Ananda Wulan Noverita; Dhea Amelia Az Zahra; Devana Retno Cahyani; Wike Azidah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Islamic boarding schools are traditional Islamic educational institutions that not only serve as centers for religious learning but also hold strategic potential in empowering the community economically. One tangible manifestation of the pesantren’s economic self-sufficiency efforts is the establishment of business units such as Mahira Mini Market, which operates under the auspices of Pondok Pesantren Mamba’ul Khoiriyatil Islamiyah (PP MHI) in Bangsalsari, Jember. This study aims to examine the planning and development strategies of the Mahira business as part of implementing an economic plan based on pesantren self-reliance and community empowerment. Using a qualitative approach and case study method, data were collected through observation, in-depth interviews, and documentation involving the pesantren’s caretakers and alumni. The findings show that PP MHI possesses sufficient physical, intellectual, and financial capital to support the development of the Mahira business. A SWOT analysis reveals that Mahira has strengths in terms of internal human resources and social support, but still faces challenges related to digitalization and marketing. The business development planning focuses on optimizing available resources, including activating social media managed by digitally skilled students (santri), as well as adding light services such as mobile credit top-ups and e-wallet transactions. The development strategies include sales digitalization, capacity building for santri, partnerships with MSMEs and alumni, and routine evaluations based on sharia principles and financial accountability. The study concludes that gradually strengthening the Mahira business can serve as a model of Pesantren-Owned Enterprises (BUMP) that is adaptive, sustainable, and replicable in other pesantren to strengthen the ummah’s economy.